Analysis of Science Literacy Skills of Chemistry Education Students in Acid-Base Topics - Eny Enawaty; Erlina Erlina (Universitas Lampung, 2021)
The purpose of this study was to determine the science literacy skills of chemistry education students in Acid-Base solution topics. The research method used is descriptive by using purposive sampling technique. The sample in this study were 22 (out of 91) year 3 students of chemistry education Department. Data collection techniques used in this study are the measurement techniques in the form of open-questions and interview techniques. The results of data analysis show that chemistry education students in solving acid-base problems; science literacy content is in the medium category, the science process is still low, and the context of scientific literacy is also low. The conclusion is the average literacy skills of chemistry education students in acid-base material is in the medium group.Keywords: analysis, science literacy skills, acid-base.